Information Technology, Globalization Through Research and Social Development - Sidhu, Lovedeep Singh; Sharma, Jyoti; Shiny; Shivani (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Globalization of science and technology is an integral aspect of globalization per se. The main engine of globalization is assumed to be the global economy propelled by global trade and technology transfers, the latter as aspects of globalization of science and technology. International trade and technology transfers are the engines that drive global economy. Much has been written on these drivers but relatively little on what drives globalization of science and technology which constitutes the backbone of international technology transfers. I attempt to fill this knowledge gap by suggesting that the drivers behind globalization of science and technology are the emerging global centers of collaborative research and development (R&D). “Science” throughout this article means both science and technology as the two closely related aspects of the same knowledge system.